RESEARCH ON THE CHARACTERISTICS OF THE POETICAL IMAGE OF "BIRD" IN THE POETRY OF HALIMA KHUDOIBERDIYEVA - Yuldasheva Dilnoza Bekmurodovna; Saliyev Abrorxon Raxmatovich; Jumaqulov Suxrob Shodiyor oʻgʻli (Web of Journals Publishing, 2024)
This article analyzes the use of bird names (ornithonyms), their functional and stylistic features, as well as their role in expanding the possibilities of the Uzbek ornithological imagination in the works of Halima Khudoiberdieva, one of the largest representatives of Uzbek poetry of the twentieth century.
Keywords: Halima Khudoiberdyeva, poetry, visual media, bird, bird, nightingale, eagle.